Facile method of raising the LTP content in Mn-Bi alloys by using sequential separation techniques for Bi and Mn. (December 2022) - Roman, Tiberiu; Murgulescu, Iulian-Ioan; Ababei, Gabriel; Stoian, George; Lostun, Mihaela; Porcescu, Marieta; Grigoras, Marian; Lupu, Nicoleta
Abstract: Mn-Bi alloys, especially the Low Temperature Phase belonging to the P6 3 /mmc crystallographic space group are an attractive alternative for replacing the rare-earth permanent magnets especially at elevated temperatures. The encountered issues during the fabrication are driven by phase segregation effects and inhomogeneities that are difficult to control or eliminate, thus leading to low experimental reproducibility and uncorrelated results for structural and magnetic properties. To overcome these issues, we propose an innovative method to increase the content of LTP by integrating an intermediary separation process during the manufacturing of Mn-Bi melt-spun ribbons. The method consists of two steps: one for Bi excess removal and the second for Mn excess removal. Bi excess removal is achieved by using a system of quartz tubes arrays though gravitational separation. This method is suitable for obtaining Mn-Bi ribbons with high content LTP, as the removal of Mn excess from the alloy occurs during the ribbons formation through the melt spinning technique. As the method employs the removal of the excess unalloyed metals, the global weight yield is in range of 53–64 wt%, but it can be increased by recovering the metallic elements and reprocess them. After a proper thermal treatment of the as quenched Mn-Bi melt-spun ribbons, over 99.0 wt% is represented by the LTP crystallographic phase characterized by saturation magnetization (MS ) values of 70.6 emu/g. Graphical Abstract: ga1 Highlights: Process development for high purity Mn-Bi alloys. Preferential content increase of low temperature phase (LTP) in Mn-Bi ribbons. Sequential separation of unalloyed Bi and Mn metallic components. Correlation between wt% of LTP and its magnetic properties.